Memorial dedicated to John Watson - Ghosh, Ayan (2023)
Memorial dedicated to John Watson, Superintendent of the Marines and Commander-in-Chief of the naval force that attacked Salsette in 1774. He participated in the Siege of Thane and was mortally wounded on 21st December 1774 and died from his wounds six days later on 27th December, at the age of 52. In 1777, the monument was erected in his honor by the East India Company.